THE AUTOMATISM OF THE DIGESTIVE TRACT ESPECIALLY IN THE EARLY FETAL STAGE AND IN THE SO-CALLED “GANGLION-FREE” CAT'S INTESTINE - TAKITA, Shuhei (Japanese Journal of Smooth Muscle Research, 1967)
In the digestive tract of the human embryo, it was confirmed previously that circular muscle first became demonstrable under light microscope which was then followed by the development of longitudinal muscle with intramural plexus between 6th and 9th week of the fetal life. The present work deals with the electron microscopic findings of the digestive tract in 10 human embryos. There was evidence to show that nerve cells, presumably those of the Auerbach's plexus and their axon structure, were demonstrated in embryos of 12mm in length (6th fetal week) in the absence of discernible muscular structure. This finding is of considerable interest in the functional anatomy of the Auerbach's plexus. It was shown in microscopic cinematography that peristalsis of the fetal digestive tract initiated with the development of circular muscle. Conduction of peristalsis, however, was not directional. A divergent propagation of two peristaltic rings from a single contraction ring was demonstrated in the small intestine. One of the characteristic findings of the fetal alimentary tract was that contraction could occur anywhere along the digestive tract and peristalsis might pass in either direction. At this time of embryological development, nerve elements, particularly intramural nerves, were present in the intestinal wall of the fetus. Action potentials recorded from a cat's “nerve-free” ring muscle tube showed that contractions could propagate in either isoor anti-peristaltic direction. The mode of contraction was considered to be quite similar to that of the fetal digestive tract. Practically identical result was obtained with a “nerve-free” ring muscle tube treated with tetrodotoxin. With preparations of circular and longitudinal muscle layers devoid of mucosa and submucosal structure, iso-peristaltic conduction was more dominant. Anti-peristalsis was found to disappear approximately after the 30th week of the fetal life. It is reasonable, therefore, to suppose that the Auerbach's plexus demonstrated in an early fetal stage was not actively participating in the regulation of the peristaltic direction.